Lo sguardo, il canto e le luci dell’universo. Forme della letteratura ecologica nella trilogia animalista di Anna Maria Ortese - Rossi Orts, Chiara (L’ospite ingrato, 2021)
The article attempts to explore the question of Ortese’s ecological sensitivity, asking how the novels L’Iguana, Il cardillo addolorato and Alonso e i visionari (also known as trilogia animalista) can be considered “ecological” works not only for the presence in them of characters with animal features and the concern about animal-rights that the author expresses in the writings of Corpo celeste and Le Piccole Persone. Starting from the analysis of Il cardillo addolororato, the essay proposes an interpretation that can also be applied to L’Iguana and Alonso e i visionari: the complexity of the narrative structure of the novels is aimed at reshaping the purely human element of the plot and leads the reader to adopt a renewed, defamiliarized, non-anthropocentric perspective on the facts narrated and, more generally, on human reality. The article concludes by proposing some observations on the possible unity and precocity of the project of the trilogia animalista and on the fundamental role given by Ortese to literature and art, fundamental ways not only to express her personal ecological sensitivity, but also to reveal and pass on this sensitivity to the readers.